2013
DOI: 10.1007/s11999-012-2724-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Surgical Treatment of Pathologic Proximal Femur Fractures Among Musculoskeletal Tumor Society Members

Abstract: Background Several strategies for the treatment of pathologic proximal femur fractures are practiced but treatment outcomes have not been rigorously compared. Questions/purposes Major variations in the use of intramedullary fixation, extramedullary/plate-screw fixation, and endoprosthetic reconstruction techniques for pathologic proximal femur fractures in patients with skeletal metastases are reported. The clinical and surgical variables that influence this choice differ among treating surgeons. To characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 18 publications
0
51
0
1
Order By: Relevance
“…We also believe that performing surgery semielectively for prophylactic purposes may provide less inherent risk for complications than operating on a fracture and performing unplanned surgery urgently, which was reported in one fracture study [3]. Steensma et al [21,22] reported that patients sustaining a pathologic fracture treated with arthroplasty had fewer treatment failures and revision surgeries than those treated with internal fixation. Because of improved outcomes with arthroplasty in pathologic fractures, trends are shifting toward treating more patients with pathologic fractures with joint replacements (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We also believe that performing surgery semielectively for prophylactic purposes may provide less inherent risk for complications than operating on a fracture and performing unplanned surgery urgently, which was reported in one fracture study [3]. Steensma et al [21,22] reported that patients sustaining a pathologic fracture treated with arthroplasty had fewer treatment failures and revision surgeries than those treated with internal fixation. Because of improved outcomes with arthroplasty in pathologic fractures, trends are shifting toward treating more patients with pathologic fractures with joint replacements (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Endoprosthetic reconstruction is a surgical modality commonly used to reach these goals, but the outcomes of specific approaches such as stem length, cement use, and Table 3. type of prosthesis continue to be controversial [15,31,35]. This study seeks to elucidate the survival, functional outcomes, and complications associated with long stem cemented hemiarthroplasty in a small group of patients treated for impending and actual pathologic fractures of the proximal femur resulting from metastatic bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pathologic fracture, therefore, is intended to restore function of the affected limb, relieve pain, improve quality of life, and facilitate custodial care as well as additional medical testing and treatment as quickly as possible. Substantial variation exists in approaching treatment for impending or actual pathologic fractures of the proximal femur [31]. Surgical interventions for pathologic fractures of the proximal femur resulting from metastatic bone disease traditionally include fixation with intramedullary nailing supplemented with polymethylmethacrylate bone cement, osteosynthesis with a plate-screw construct and polymethylmethacrylate, or endoprosthetic reconstruction [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these are caused by metastatic disease, and these fractures cause pain, morbidity, and in some patients, premature death. In a survey of members of the Musculoskeletal Tumor Society (MSTS) presenting multiple clinical scenarios, a wide range was noted in the preferred treatments, including intramedullary nail fixation, proximal femur resection and reconstruction, cemented hemiarthroplasty, and open reduction internal fixation [2]. Furthermore, there was a nearly equal split regarding the use of polymethyl methacrylate around intramedullary nails.…”
mentioning
confidence: 99%